A study on consumer awareness and purchasing behavior of finger millet products in Coimbatore - Monika, K; Samsai, T; Velavan, C; Parimalarangan, R; Ramalingam, G S (Plant Science Today, 2025)
This study investigates consumer awareness and preferences for finger millet (Eleusine coracana) products in Coimbatore, Tamil Nadu, India. As a nutritionally dense cereal crop, finger millet has gained attention for its potential to address malnutrition and lifestyle diseases. The research assessed awareness of its nutritional benefits, factors driving purchasing decisions and product preferences among urban consumers. A structured questionnaire-based survey was conducted with 150 respondents selected through simple random sampling. The study revealed higher awareness levels of finger millet's nutritional value among younger (21-30 years, 51.64 % highly aware) and female (39.77 % highly aware) consumers. Factor analysis identified product-related aspects, such as nutritional value and convenience, as key influencers in purchasing decisions, explaining 45.19 % of the variance. Preferred product forms included finger millet flour (23 %), noodles (20 %) and porridge (18 %). So, companies should focus on diversifying the millet flour category to attract consumers easily. Garrett's ranking positioned finger millet as the most favoured millet (score 69.5), followed by proso millet (66.0) and little millet (63.0). These findings provide valuable insights for agricultural researchers, plant breeders and food technologists to align crop improvement strategies and product development with consumer preferences. Companies should prioritize marketing to female consumers, who demonstrate higher awareness. Following this, they should focus on younger consumers (21-30 years), who also show significant interest. Marketing strategies should include creating innovative snack items designed to appeal to children, paired with vibrant and engaging marketing campaigns that capture their attention. Additionally, strategies should target health-conscious individuals and male consumers by highlighting finger millet's contribution to overall wellness and emphasizing that finger millet is a versatile food suitable for all demographics and dietary preferences.